Asphalt-based closed-pore carbon material, preparation method thereof and sodium ion battery
Through pre-oxidation, low-temperature carbonization and activation treatment, combined with asphalt impregnation and coating technology, the structure of asphalt-based carbon materials is optimized, and the problems of its sodium storage capacity and electrochemical performance are solved, achieving efficient performance improvement of the negative electrode material of sodium ion battery , provides a reliable industrialization path for sodium ion batteries.
Patent Information
- Application Number
- CN202411403305.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Asphalt-based carbon materials have low sodium storage capacity in sodium ion batteries and are difficult to control the structure, resulting in poor electrochemical performance, especially the initial Coulomb efficiency, which is difficult to meet the requirements of high-performance batteries.
Treatment of asphalt-based carbon sources through preoxidation and low-temperature carbonization, gas activation and chemical activation are introduced to form porous carbon materials, and closed-porous structures are formed through asphalt impregnation coating, optimizing pore structure and surface properties, and improving sodium storage performance.
Asphalt-based closed-porous carbon materials with high capacity, high first-time efficiency and high stability cycle are achieved, which significantly improves the electrochemical performance of sodium ion batteries and promotes the industrial application of materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of negative electrode materials for sodium ion batteries, and in particular relates to an asphalt-based closed-cell carbon material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] In sodium-ion batteries, amorphous carbon materials have become the most promising negative electrode materials due to their abundant resources, diverse structures, and excellent comprehensive performance. The high cost and low carbon yield of biomass and synthetic resins restrict the cost of sodium-ion batteries. In order to reduce battery costs, low-cost precursors with high carbon yields are needed. Asphalt is expected to become a commercial negative electrode material for sodium-ion batteries.
[0003] However, the sodium storage capacity of asphalt-based carbon materials is low, mainly because asphalt is a soft carbon precursor. During the high-temperature pyrolysis and carbonization process, the molecules are orderly rearranged to form a graphite-like layer structure, which is not conducive to the storage of sodium ions. In addition, asphalt has a complex chemical composition, which has a great negative impact on the structure and composition of the final carbon material. Due to the existence of the above situation, it is difficult to control the structure of the final carbon material during the asphalt conversion process.
[0004] Therefore, some researchers have introduced templates such as magnesium oxide, calcium oxide, silicon dioxide and molten salt into the system to adjust the pore structure and morphology of asphalt-based carbon materials. However, this template method introduces other impurities, which require tedious subsequent acid or water washing operations to remove. In addition, the pores formed by the template exist in the form of macropores, which makes it impossible for sodium ions to be effectively filled. At the same time, during the charge and discharge process, a large solid electrolyte interface film will be formed in the macropores, which consumes the electrolyte excessively. Therefore, it is not conducive to sodium storage.
[0005] In addition to the template method, oxidation strategies have also been developed to prepare asphalt-based porous carbon. During this process, functional groups are introduced into the asphalt molecules to increase their reactivity. Subsequently, the molecules react to form macromolecules similar to the graphite structure, which avoids phase changes during pyrolysis and enhances the structural stability of the intermediate products. Since the morphology of carbon materials can be well controlled, the asphalt oxidation method has become an important strategy for preparing carbon materials. However, the electrochemical properties of carbon materials prepared by the asphalt oxidation method, especially the specific capacity, can easily reach the upper limit and cannot meet the requirements for high-performance batteries. In addition, the initial coulombic efficiency is low, and modification and optimization measures are required.
[0006] A large number of studies have shown that the electrochemical energy storage performance of carbon materials depends largely on their surface properties such as pore structure. At the same time, heteroatom doping is also a relatively efficient method to improve the sodium storage performance of asphalt-based carbon. Therefore, optimizing pore engineering and heteroatom doping are effective strategies to solve the poor capacity and low initial coulombic efficiency of asphalt-based carbon materials. For pore engineering, it is crucial to control the pore structure (including pore volume, diameter and its distribution). Energy storage carbon materials generally have micropores, mesopores and macropores. Micropores play a major role in the sodium storage of carbon materials and can provide abundant active sites for the adsorption of electrolyte ions, but micropores are usually open, which will consume a large amount of electrolyte ions, resulting in reduced battery performance. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a pitch-based closed-cell carbon material and a preparation method thereof and a sodium ion battery. The pitch-based closed-cell carbon material has the advantages of high capacity, high initial efficiency and high stable cyclability.
[0008] The present invention is achieved through the following technical solutions: The present invention provides a method for preparing a pitch-based closed-cell carbon material, comprising the following steps: S1, pre-oxidizing the asphalt-based carbon source in an oxidizing gas atmosphere at 200-350° C. to obtain a pre-oxidized product; S2, low-temperature carbonizing the pre-oxidation product at 300-800° C. under an inert atmosphere to obtain a first precursor; S3, gas-activating the first precursor in an activated gas atmosphere to obtain a second precursor; S4, chemically activating the second precursor using a chemical activator to obtain a porous carbon material; S5, impregnating the porous carbon material in the asphalt solution, and then separating and drying to obtain a blank; S6, carbonizing the blank under the protection of an inert gas to obtain a pitch-based closed-cell carbon material.
[0009] Preferably, in S1, the asphalt-based carbon source is one or a mixture of two or more of coal tar asphalt, petroleum asphalt and natural asphalt.
[0010] Preferably, in S1, the pre-oxidation time is 6-48 hours, and in S2, the low-temperature carbonization time is 2-6 hours.
[0011] Preferably, in S3, the activation gas is at least one of carbon dioxide, oxygen, ozone, sulfur dioxide, sulfur trioxide, nitrogen dioxide, water vapor and magnesium vapor.
[0012] Preferably, in S3, the temperature of gas activation is 400-800°C.
[0013] Preferably, in S4, the chemical activator is one of potassium hydroxide, phosphoric acid, zinc chloride and potassium carbonate.
[0014] Preferably, in S5, the blank is subjected to repeated immersion, separation and drying operations 1-5 times.
[0015] Preferably, in S6, the carbonization temperature is 1000-1600° C. and the time is 1-5 h.
[0016] The present invention provides a pitch-based closed-cell carbon material obtained by the preparation method as described above.
[0017] The present invention provides a sodium ion battery, comprising a negative electrode, wherein the negative electrode comprises the asphalt-based closed-cell carbon material according to claim 9.
[0018] Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the asphalt-based closed-cell carbon material of the present invention comprises: low-temperature oxidation and low-temperature carbonization of the asphalt-based carbon source to obtain a first precursor, gas activation and chemical activation of the first precursor to obtain a porous carbon material; then high-energy ball milling is used to assist the organic solvent in efficient extraction to prepare the impregnation asphalt, and the porous carbon material obtained is subsequently modified by the liquid asphalt impregnation method, and the dried material is heated in an inert gas atmosphere for high-temperature carbonization to obtain a precisely controlled ultra-stable negative electrode material with a rich closed-cell structure. First, the present invention uses pre-oxidation and low-temperature carbonization to treat the asphalt-based carbon source, and the pre-oxidation process brings in oxygen groups to promote cross-linking between carbon structure molecules. The low-temperature carbonization process further optimizes the configuration of oxygen-containing functional groups in the carbon material, which can prevent the material from being graphitized due to high-temperature carbonization, thereby increasing the sodium storage capacity of the platform area. Secondly, the present invention increases the sodium storage sites by introducing gas activation and chemical activation to form pores, and the gas activation will optimize the pore structure of the material so that it has more closed-cell structures. The chemical activation process will further optimize the surface of the carbon material, and the chemical activation process can cooperate with doping or cross-linking to further improve the sodium storage performance. Compared with a single activation, the electrochemical performance of the carbon material formed by the cooperation of two activations is better. Again, the present invention performs asphalt impregnation and coating on the porous carbon material, and the asphalt enters the pores of the porous carbon material, so that a part of the pores originally generated in the two activations are open. After the impregnation treatment, the outer asphalt layer is coated to obtain a closed pore with tightened pores. At the same time, this closed-pore structure with tightened pores will be a rational space for sodium ion filling. At the same time, because the closed-pore structure can fill a large amount of sodium ions without excessive consumption of electrolyte, its electrochemical performance can be effectively improved. The outer modified layer formed by impregnation and coating can increase the sodium ion transmission rate, and improve the initial coulomb efficiency and rate performance of the material. The synergy of various optimization measures of the present invention will greatly improve the performance of the asphalt-based carbon negative electrode, prompting it to accelerate the pace of industrialization, and provide a reliable path for the design of negative electrode materials and functional industrialization of sodium ion batteries.
[0019] Furthermore, through multiple impregnation modifications, the structure of the surface coating layer can be improved, significantly improving the sodium storage performance of the carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 This is a scanning electron microscope image of the closed-pore negative electrode material prepared using coal tar pitch as the carbon source in Example 9.
[0022] Figure 2 This is a charge and discharge curve diagram of the closed-pore negative electrode material prepared using coal tar pitch as the carbon source in Example 9. DETAILED DESCRIPTION
[0023] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0024] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0025] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0026] The method for preparing the pitch-based closed-cell carbon material of the present invention comprises the following steps: S1, placing the asphalt-based carbon source in an oxidizing gas atmosphere, and performing a pre-oxidation treatment at 200-350° C. for 6-48 hours to obtain a pre-oxidation product; S2, subjecting the pre-oxidation product to low-temperature carbonization at 300-800° C. for 2-6 hours under an inert atmosphere to obtain a first precursor; S3, gas-activating the first precursor in an activated gas atmosphere to obtain a second precursor; S4, chemically activating the second precursor using a chemical activator to obtain a porous carbon material; S5, impregnating the porous carbon material in the asphalt solution, and then separating and drying to obtain a blank; S6, carbonizing the blank under the protection of an inert gas to obtain a pitch-based closed-cell carbon material.
[0027] In S1 of the present invention, the asphalt-based carbon source is asphalt with a softening point of 80-300°C, such as coal tar asphalt, petroleum asphalt and natural asphalt, or a mixture of two or more thereof. The pre-oxidation temperature is more preferably 300-325°C.
[0028] In S2 of the present invention, the first precursor can also be crushed by a crusher to obtain a crushed material for S3. The crushing is performed by air flow milling, mechanical milling, fluidized bed milling or ball milling. The crushing end condition is that the average volume particle size of the powder is 0.2-10 μm. The crushed material has a small particle size and is useful for subsequent etching and activation. The low-temperature carbonization temperature is preferably 600-800°C.
[0029] In S3 of the present invention, the temperature of the gas activation is 400-800° C., and the activated gas includes at least one of carbon dioxide, oxygen, ozone, sulfur dioxide, sulfur trioxide, nitrogen dioxide, water vapor and magnesium vapor.
[0030] S3 of the present invention is specifically: heating the first precursor to a holding temperature, converting the inert gas into an activated gas, and the activation time is 1-12 hours.
[0031] In S4 of the present invention, the chemical activator is one of potassium hydroxide, phosphoric acid, zinc chloride, and potassium carbonate, and the mass ratio of the chemical activator to the second precursor is between 1: (1-5). The specific operation is: adding the second precursor to the chemical activator solution, stirring for 6-24 hours, washing with water until neutral, and drying.
[0032] S5 of the present invention is specifically: immersing the porous carbon material in an asphalt solution and stirring for 2-8 hours, then separating the solid and the liquid, and drying to obtain a blank. The obtained blank is repeatedly immersed and dried, and the number of immersions is 1-5 times, and more preferably 3-5 times. The asphalt solution is obtained by dissolving asphalt in a solvent, and the asphalt content is 5%-30%, and more preferably 10%-20%; the asphalt solution preparation method is: adding asphalt to a solvent, high-energy ball milling dispersion for 1-3 hours, and collecting the clear liquid after centrifugation; the solvent is at least one of tetrahydrofuran, n-hexane, xylene, toluene, quinoline, etc.
[0033] S6 of the present invention is specifically as follows: placing the blank under the protection of inert gas, heating the temperature to 1000-1600°C at a rate of 2-5°C / min, and keeping the temperature for 1-5h to obtain the carbonized blank; after screening, the asphalt-based closed-cell carbon material is obtained.
[0034] In the above method of the present invention, the inert gas includes at least one of nitrogen, argon, neon, helium, xenon and krypton; the equipment for carbonization includes at least one of a tubular furnace, a box furnace, a push plate kiln, a graphitization furnace and a roasting kiln.
[0035] The asphalt-based closed-cell carbon material is used as a negative electrode material in a sodium ion battery.
[0036] The present invention forms a highly conductive coated asphalt-based closed-cell adjustable sodium ion battery negative electrode material by low-temperature oxidation, low-temperature carbonization, crushing, gas activation pore formation, chemical activation, coating modification, and screening of an asphalt-based carbon source.
[0037] The present invention is further described below by way of examples.
[0038] Example 1 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 300°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0039] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0040] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0041] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0042] Example 2 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in a 600°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0043] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0044] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0045] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0046] Example 3 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 24h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0047] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0048] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0049] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0050] Example 4 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0051] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 4 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0052] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0053] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0054] Example 5 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0055] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 80 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0056] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0057] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0058] Example 6 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0059] The obtained crushed material is placed in a water vapor atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the water vapor gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0060] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0061] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0062] Example 7 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0063] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0064] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 20%.
[0065] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0066] Example 8 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0067] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0068] 20 g of the obtained porous carbon material was added to 1 L of asphalt solution and stirred for 8 h, then filtered and dried to obtain a blank; the blank was repeatedly impregnated and dried for 2 times. The preparation method of the asphalt solution is as follows: petroleum asphalt is added to tetrahydrofuran, high-energy ball milling is dispersed for 2 h, and the supernatant is collected after centrifugation at 8000 rpm for 10 min, and the asphalt content is 10%.
[0069] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0070] Example 9 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0071] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0072] 20 g of the obtained porous carbon material was added to 1 L of asphalt solution and stirred for 8 h, then filtered and dried to obtain a blank; the blank was repeatedly impregnated and dried for 4 times. The preparation method of the asphalt solution is as follows: petroleum asphalt is added to tetrahydrofuran, high-energy ball milling is performed for 2 h, and the supernatant is collected after centrifugation at 8000 rpm for 10 min, and the asphalt content is 10%.
[0073] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0074] Example 10 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0075] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of phosphoric acid solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0076] 20 g of the obtained porous carbon material was added to 1 L of asphalt solution and stirred for 8 h, then filtered and dried to obtain a blank; the blank was repeatedly impregnated and dried for 5 times. The preparation method of the asphalt solution is as follows: petroleum asphalt is added to tetrahydrofuran, dispersed by high-energy ball milling for 2 h, centrifuged at 8000 rpm for 10 min, and the supernatant was collected, and the asphalt content was 10%.
[0077] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0078] Embodiment 11 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0079] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40mL / min; the second precursor is placed in a 30gKOH solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0080] Take 20g of the obtained porous carbon material and add it to 1L of asphalt solution and stir for 8h, then filter and dry to obtain a blank; the preparation method of the asphalt solution is: add petroleum asphalt to tetrahydrofuran, high-energy ball milling dispersion for 2h, centrifuge at 8000rpm for 10min, collect the supernatant, and the asphalt content is 10%.
[0081] The obtained blank was heated to 1400°C at a heating rate of 5°C / min under the protection of inert gas and kept warm for 2 hours to obtain a carbonized blank; after screening through a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0082] Example 12 A method for preparing a pitch-based closed-cell carbon material, the method comprising the following steps: 30g of coal tar pitch was placed in an air atmosphere and pre-oxidized at 325°C for 12h, and then the pre-oxidized product was placed in an 800°C carbonization furnace for low-temperature carbonization to obtain a first precursor; the obtained first precursor was crushed by a crusher to obtain a crushed material with a particle size of 0.5-10μm.
[0083] The obtained crushed material is placed in a carbon dioxide atmosphere and gas activated at 800°C for 2 hours to obtain a second precursor, wherein the carbon dioxide gas flow rate is 40 mL / min; the second precursor is placed in 30 g of potassium carbonate solution, stirred for 6 hours, chemically activated, washed with water to neutrality, and dried to obtain a porous carbon material.
[0084] 20 g of the obtained porous carbon material was added to 1 L of asphalt solution and stirred for 8 h, then filtered and dried to obtain a blank; the preparation method of the asphalt solution was as follows: petroleum asphalt was added to tetrahydrofuran, dispersed by high-energy ball milling for 2 h, centrifuged at 8000 rpm for 10 min, and the supernatant was collected, and the asphalt content was 10%.
[0085] The obtained blank was placed under inert gas protection, heated to 1400°C at a rate of 5°C / min, and kept warm for 2 hours to obtain a carbonized blank; after screening with a 325-mesh sieve, a hard carbon negative electrode material for a sodium ion battery was obtained.
[0086] Comparative Example 1 It is basically the same as Example 9, except that the temperature in "placing the pre-oxidation product in a carbonization furnace at 800°C for low-temperature carbonization" is modified to 1200°C.
[0087] Comparative Example 2 It is basically the same as Example 9, except that chemical activation is not performed, and the second precursor is directly added into 1L of asphalt solution for subsequent same treatment.
[0088] Comparative Example 3 It is basically the same as Example 9, except that the asphalt solution impregnation and subsequent treatment are not performed, and the porous carbon material obtained by chemical activation is directly used as the final negative electrode material.
[0089] In order to more intuitively demonstrate the performance of the material prepared in the present invention, the following table lists the preparation parameters and electrochemical properties of the negative electrode materials prepared in some of the above examples.
[0090] At the same time, in order to test the electrochemical properties of the asphalt-based negative electrode materials prepared in the embodiments and comparative examples, the embodiments and comparative examples were used to prepare the negative electrode of the sodium ion battery. The specific preparation method was as follows: the asphalt-based negative electrode material, conductive carbon black and sodium alginate were put into a mortar at a mass ratio of 8:1:1 and ground, an appropriate amount of ultrapure water was added, ground until homogeneous, transferred to copper foil, coated on the copper foil with a 100 μm coater, placed in a vacuum drying oven at 85° C. and vacuum dried for 12 h, and prepared into a disc electrode with a diameter of 14 mm using a punching machine to obtain a negative electrode material electrode sheet. The electrode sheets were compacted on a sheet press, and the battery was assembled in a glove box filled with high-purity argon according to the structure of the CR2016 standard button cell, wherein a glass fiber disc with a diameter of 19 mm was used as a diaphragm, a sodium metal sheet with a diameter of 12 mm and a thickness of 0.2 mm was used as a counter electrode and a reference electrode, and 1 mol / L sodium hexafluorophosphate EC-DEC-EMC was used as an electrolyte. After standing for 8 h, the battery was charged and discharged at a current density of 30 mA / g on a blue battery test platform. Figure 2 shown.
[0091] Among them, the environmental field emission scanning electron microscope uses the Thermo Fisher Scientific company's sodium electron microscope, which can work in a relatively humid or low vacuum environment, so that the sample can maintain its original state in the scanning electron microscope, avoiding deformation, cracking and other problems caused by drying or vacuum treatment. SEM scans the sample surface through a transmitted electron beam, and uses the principles of electron reflection, transmission, and scattering to obtain information such as the sample's morphology, structure, and element distribution, and can display these details at a high resolution (level), such as Figure 1 shown.
[0092] The electrochemical performance test results of the asphalt-based negative electrode materials prepared in various embodiments and comparative examples are shown in Table 1.
[0093] Table 1 Electrochemical performance test results of pitch-based hard carbon anode materials
[0094] By comparing Example 9 with Comparative Example 1, it can be seen that the electrochemical performance of the obtained material is greatly different when the low-temperature carbonization temperature is changed to 1200°C. The main reason is that low-temperature carbonization has the function of optimizing and screening the configuration of oxygen-containing functional groups, increasing the carbon-oxygen double bond content, which is beneficial to the cross-linking of asphalt materials, preventing their graphitization, and enhancing the sodium storage performance.
[0095] By comparing Example 9 and Comparative Example 2, it can be seen that the chemical activation effect is significant, and the synergistic effects of doping and cross-linking on the basis of pore formation effectively improve the sodium storage capacity.
[0096] By comparing Example 9 and Comparative Example 3, it can be seen that the asphalt impregnation coating of the porous carbon material can significantly improve the reversible specific capacity and the initial coulombic efficiency. This is because the asphalt enters the pores of the porous carbon material, so that a part of the open pores originally generated by the two activations are obtained after the impregnation treatment. The closed pore structure with tightened pores will be a rational space for sodium ion storage. The outer modification layer formed by the impregnation coating can increase the sodium ion transmission rate and improve the initial coulombic efficiency and rate performance of the material.
[0097] From the above, it can be seen that the asphalt-based carbon source is treated by pre-oxidation and low-temperature carbonization. The pre-oxidation process brings in oxygen groups, which promotes cross-linking between carbon structure molecules. The low-temperature carbonization process further optimizes the configuration of oxygen-containing functional groups in the carbon material, which can prevent the graphitization of the material caused by high-temperature carbonization, thereby increasing the sodium storage capacity of the platform area. Secondly, the present invention increases the sodium storage sites by introducing gas activation and chemical activation to form pores, and gas activation will optimize the pore structure of the material to make it have more closed-pore structures. The chemical activation process will further optimize the surface of the carbon material, and the chemical activation process can cooperate with doping or cross-linking to further improve the sodium storage performance. Compared with single activation, the electrochemical performance is better. Thirdly, the present invention performs asphalt impregnation and coating on the porous carbon material, and the asphalt enters the pores of the porous carbon material, so that a part of the open pores originally generated in the two activations are obtained. After the impregnation treatment, the closed pores with tightened pores are obtained. At the same time, this closed-pore structure with tightened pores will be a rational space for sodium ion storage. The number of asphalt impregnations significantly affects the thickness of the outer coating layer, which is very important for the balance between sodium storage capacity and rate performance. When impregnated four times, the performance is better.
[0098] Figure 1 This is a scanning electron microscope image of the closed-cell negative electrode material prepared using coal tar pitch as the carbon source in Example 9. It can be seen from the image that the obtained pitch-based carbon material has an amorphous structure and a relatively suitable pitch coating layer exists on the surface.
[0099] Figure 2 This is the charge and discharge curve diagram of the closed-cell negative electrode material prepared using coal tar pitch as the carbon source in Example 9. Compared with other samples, it has more ideal sodium storage performance and initial coulombic efficiency, a reversible specific capacity of 300.56 mAh / g, and an initial efficiency of 93.02%.
[0100] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0101] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a pitch-based closed-cell carbon material, characterized in that: The following steps are involved: S1, pre-oxidizing the asphalt-based carbon source in an oxidizing gas atmosphere at 200-350° C. to obtain a pre-oxidized product; S2, low-temperature carbonizing the pre-oxidation product at 300-800° C. under an inert atmosphere to obtain a first precursor; S3, gas-activating the first precursor in an activated gas atmosphere to obtain a second precursor; S4, chemically activating the second precursor using a chemical activator to obtain a porous carbon material; S5, impregnating the porous carbon material in the asphalt solution, and then separating and drying to obtain a blank; S6, carbonizing the blank under the protection of an inert gas to obtain a pitch-based closed-cell carbon material.
2. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S1, the asphalt-based carbon source is one or a mixture of two or more of coal tar pitch, petroleum pitch and natural asphalt.
3. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S1, the pre-oxidation time is 6-48 h, and in S2, the low-temperature carbonization time is 2-6 h.
4. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S3, the activation gas is at least one of carbon dioxide, oxygen, ozone, sulfur dioxide, sulfur trioxide, nitrogen dioxide, water vapor and magnesium vapor.
5. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S3, the temperature of gas activation is 400-800°C.
6. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S4, the chemical activator is one of potassium hydroxide, phosphoric acid, zinc chloride and potassium carbonate.
7. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S5, the blank is repeatedly subjected to the operations of dipping, separation and drying 1-5 times.
8. The method for preparing a pitch-based closed-cell carbon material according to claim 1, characterized in that: In S6, the carbonization temperature is 1000-1600°C and the time is 1-5h.
9. A pitch-based closed-cell carbon material obtained by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: It comprises a negative electrode, wherein the negative electrode comprises the pitch-based closed-cell carbon material according to claim 9.
Citation Information
Patent Citations
Asphalt-based spherical activated carbon as well as preparation method and application thereof
CN113912059A
High-power asphalt-based sodium ion battery carbon negative electrode material as well as preparation method and application thereof
CN117125694A
Sodium-ion battery hard carbon negative electrode material with high compaction density and low specific surface area and preparation method of sodium-ion battery hard carbon negative electrode material
CN117361496A
Preparation method of hollow mesoporous activated carbon
CN118221114A
Preparation method of coal-based carbon material for sodium ion battery negative electrode
CN118343755A
Cited By
Preparation method of spherical pitch-based hard carbon and sodium ion battery
CN120463195A
A method for preparing a spherical pitch-based hard carbon and a sodium-ion battery
CN120463195B
High-performance asphalt-based porous carbon as well as preparation method and application thereof
CN121020582A
Porous carbon with directional slit pores as well as preparation method and application of porous carbon
CN121377017A
Porous carbon having oriented slit pores and method of making and use thereof
CN121377017B